Multi-Objective Power Minimization Design for Energy Efficiency in Multicell Multiuser MIMO Beamforming System - Chen, Wei-Yu; Hsieh, Po-Ya; Chen, Bor-Sen (IEEE transactions on green communications and networking, 2020)
In this study, we propose a multi-objective power optimization design in a multicell multiuser multiple-input multiple-output (MIMO) beamforming system in the future era of green communications for energy efficiency. First, we consider a multicell multiuser MIMO system with multiple base stations (BSs) and each BS could serve multiple downlink mobile stations (MSs) simultaneously. Second, we formulate a multi-objective optimization problem (MOP) to simultaneously minimize the downlink powers of different groups of cells subject to the signal to interference plus noise ratio (SINR) constraints. An indirect method is proposed to transform the MOP of multi-objective power minimization design of multicell multiuser MIMO beamforming system to a semidefinite programming (SDP)-constrained MOP. In order to efficiently solve the multi-objective power minimization problem with a low computational complexity, a novel multi-objective evolutionary algorithm (MOEA) with modification is proposed to guarantee the global convergence of Pareto optimal solutions. Finally, simulation results are provided to validate the performance and show the superiority of the proposed multi-objective beamforming green design to minimize the downlink power consumption of MIMO beamforming system in different groups of cells simultaneously.